Chapter Il carattere di Jules Michelet - Nacci, Michela (Studi e saggi, 2020)
The article deals with the national character in Jules Michelet. Michelet supports an essentialist version of the character. According him, it is caused by natural elements: geography, food and the various regions that make up France. These elements are spiritualized over time: it is the history that gave rise to the character of the French. The result is the complete fusion of all differences in a nation-individual: a generous person towards humanity. The French character is contrasted with the English character: selfish, greedy, all devoted to work and earnings. It is precisely because of their different characters that France has given the world the Revolution and England the Industrial Revolution, a phenomenon that mechanizes work, that destroys the body and soul of the workers.